Antibiotic Resistance Among Salmonella spp. Isolated from Feces of Patients with Acute Diarrhea in Gwangju Area, Korea, during 2000-2009 - Kim, T.S., Public Health and Environment Institute of Gwangju, Gwangju, Republic of Korea; Kim, M.J., Public Health and Environment Institute of Gwangju, Gwangju, Republic of Korea; Kim, S.H., Public Health and Environment Institute of Gwangju, Gwangju, Republic of Korea; Seo, J.J., Public Health and Environment Institute of Gwangju, Gwangju, Republic of Korea; Kee, H.Y., Public Health and Environment Institute of Gwangju, Gwangju, Republic of Korea; Chung, J.K., Public Health and Environment Institute of Gwangju, Gwangju, Republic of Korea; Kim, E.S., Public Health and Environment Institute of Gwangju, Gwangju, Republic of Korea; Moon, Y.W., Public Health and Environment Institute of Gwangju, Gwangju, Republic of Korea; Ha, D.R., Public Health and Environment Institute of Gwangju, Gwangju, Republic of Korea; Kim, M.K., Namseoul University, Cheonan, Republic of Korea; Lim, S.K., Animal and Plant Quarantine Agency, Gyeonggi-do, Republic of Korea; Nam, H.M., Animal and Plant Quarantine Agency, Gyeonggi-do, Republic of Korea (The Korean Journal of Microbiology, 2013)
Antibiotic susceptibility was examined for 596 Salmonella isolates from patients with acute gastroenteritis during 2000-2009 in Gwangju area in South Korea. Of 16 antibiotics tested, ampicillin resistance (43%) was the most commonly observed resistance among the 596 Salmonella sp. isolates, followed by tetracycline (35.9%), nalidixic acid (31.5%), and chloramphenicol (26.2%). Antibiotic resistance varied among serotypes: The highest resistance of S. Enteritidis and S. Typhimurium was to ampicillin (51.1%) and tetracycline (77.9%), respectively. A total of 89 resistance patterns were observed, and 26% (155/596) of Salmonella isolates were susceptible to all antibiotics tested in this study. About 21% (127/596) and 15% (87/596) of the isolates were resistant to one and two antibiotics, respectively. The rest of Salmonella isolates (227/596, 38%) were resistant to three or more antibiotic agents. The highest multi-drug resistance (MDR) was observed in serotype S. Paratyphi B (76.5%), followed by S. Typhimurium (58.2%), and S. Enteritidis (40.2%). The most common resistance pattern of MDR isolates was ampicillinchloramphenicol- nalidixic acid-ticarcillin (36/227, 15.8%), most of which (35/36, 97.2%) were S. Enteritidis.